ANALISIS KINERJA KEUANGAN RSSH GPM AMBON - Anna Valensia Chrisitianty de FRETES; J.R. Pattiruhu (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
The purpose of this research is to find out the Sumber Hidup GPM Hospital(RSSH GPM) financial performance based on Direct Service Cost Ratio, Wage Cost Ratio/Employee Salary, and Administration and General Cost Ratio. This research was conducted at the Ambon City GPM Sumber Hidup Hospital. Collecting data using Field Research and Literature Research which are secondary, namely the Financial Statements of Sumber Hidup Hospital 2015 - 2017. The data analysis technique used is the Cost Ratio Analysis and Multiple Regression Analysis. The results showed that each relative ratio increased from 2015 to 2017. This is due to the increase in inpatient and outpatient income, high wages / staff costs, and high administrative and general spending. If viewed from its development, RSSH revenue is not proportional to the amount of operational financing that supports this income. This indicates that the finances of Sumber Hidup Hospital are in the Unhealthy category. In statistical testing, it proves the existence of a relationship between each ratio with the financial performance of RSSH.Keywords : Direct Service Cost Ratio, Wage Cost Ratio/Employee Salary, and Administration and General Cost Ratio=> Financial Performance, Cost Ratio